2012
DOI: 10.2214/ajr.10.6105
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Multicenter Patient Registry to Determine the Clinical Impact of Breast-Specific Gamma Imaging, a Molecular Breast Imaging Technique

Abstract: Breast-specific gamma imaging significantly contributed to the detection of malignant or high-risk lesions in patients with negative or indeterminate mammographic findings, and it provided improved management when compared with ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 11 publications
2
31
1
Order By: Relevance
“…This recall rate falls within the range of previously reported BSGI recall rates in women with benign mammograms (22,26). BSGI detected an additional 14 mammographically occult breast cancers (1.7%), or 16.5 cancers per 1,000 women screened.…”
Section: Discussionsupporting
confidence: 82%
“…This recall rate falls within the range of previously reported BSGI recall rates in women with benign mammograms (22,26). BSGI detected an additional 14 mammographically occult breast cancers (1.7%), or 16.5 cancers per 1,000 women screened.…”
Section: Discussionsupporting
confidence: 82%
“…Diagnostic breast imaging can include problem solving when vague abnormalities persist after additional mammographic views and ultrasound; but with current ultrasound equipment and tomosynthesis, it is rare to require further diagnostic imaging. Sensitivity is at least as high as ultrasound with BSGI, but specificity is higher with BSGI (17,18). In patients presenting with cancer of unknown primary cause (typically, a metastatic axillary node consistent with breast cancer), both 99m Tc-sestamibi-and 18 F-FDG-based imaging can identify the underlying breast cancer (Fig.…”
Section: The Evidencementioning
confidence: 99%
“…Moreover, in this study including 416 cases, BSGI was demonstrated to be useful in evaluating lesions difficult to biopsy and in patients who desired further testing rather than biopsy or short term follow-up of their breast abnormality. These interesting data have been then confirmed in a multicentre clinical patient registry analysis, which aimed to quantify the impact of BSGI on the management of patients with BC in clinical practice, and to identify the subgroups benefiting more from the use of this examination [8]. A total of 1,042 patients were evaluated.…”
mentioning
confidence: 90%